2002
DOI: 10.1046/j.1529-8817.2002.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

EVOLUTION OF MICROALGAE IN HIGHLY STRESSING ENVIRONMENTS: AN EXPERIMENTAL MODEL ANALYZING THE RAPID ADAPTATION OF DICTYOSPHAERIUM CHLORELLOIDES (CHLOROPHYCEAE) FROM SENSITIVITY TO RESISTANCE AGAINST 2,4,6‐TRINITROTOLUENE BY RARE PRESELECTIVE MUTATIONS1

Abstract: The increasing rates of global extinction due to human activities necessitate studies of the ability of organisms to adapt to the new environmental conditions resulting from human disturbances. We investigated the evolutionary adaptation of a microalga to sudden environmental change resulting from exposure to novel toxic chemical residues. A laboratory strain of Dictyosphaerium chlorelloides (Naum.) Kom. and Perm. (Chlorophyceae) was exposed to increasing concentrations of the modern contaminant 2,4,6‐trinitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…By means of these mechanisms, microalgae achieve adaptation toxenobiotics (García-Villada et al, 2002). In addition, Chlorophytes species were more capable of rapid adaptation to extreme environments than other algae phyla (de-Godos et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…By means of these mechanisms, microalgae achieve adaptation toxenobiotics (García-Villada et al, 2002). In addition, Chlorophytes species were more capable of rapid adaptation to extreme environments than other algae phyla (de-Godos et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has showed that TNT dissolved in water can be unhealthy to aquatic or submerged plants, green algae, and cyanobacteria, as evidenced by a variety of phytotoxicity indicators such as reduced growth or reproduction, cell viability, chlorosis, or browning (Best et al, 1999;Burken et al, 2000;French et al, 1999;Hannink et al, 2001;Lucero et al, 1999;Nipper et al, 2001;Pavlostathis et al, 1998;Pavlostathis and Jackson, 1999;Smock et al, 1976;Won et al, 1976). Inhibition of photosynthesis resulting from TNT uptake by vascular plants or marine macroalgae has not been described earlier, although one study (García-Villada et al, 2002) demonstrated that photosynthesis in the freshwater green microalga Dictyosphaerum chlorelloides decreased exponentially with increasing TNT concentration form 3 to 30 mg/L. Inhibition of photosynthesis by P. hornemannii microplantlets during TNT uptake may occur by a mechanism similar to nitroaromatic herbicide action on the photosynthetic apparatus of higher plants, where the nitro groups disrupt electron transport in photosystem I, photosystem II and form nitroxide radicals that damage chlorophyll (Dodge, 1989;Fedtke, 1982;Van Assche and Carles, 1982).…”
Section: Discussionmentioning
confidence: 95%
“…The mutation rate from formaldehyde susceptibility to formaldehyde resistance in D. chlorelloides (3.61 9 10 -6 divisions) was found to be on the same order of magnitude than mutation rates we have described for resistance to many other biocides in chlorophyta López-Rodas et al 2001;Baos et al 2002;García-Villada et al 2002), significantly higher than mutation rates for SET 1 (105 tubes) They were allowed to grow, before adding the substance in study, till they reached the number of 4.2 9 10 5 cells. Set 2 consists on 25 tubes control with 4.2 9 10 5 cells that directly incorporated the studied product.…”
Section: Resultsmentioning
confidence: 99%
“…The fluctuation test (Luria and Delbrück 1943) provides the appropriate procedure to discriminate between adaptation by selection of rare spontaneous mutations and other procedures. Recently, fluctuation test has been conducted entirely in liquid media, growing microalgae cultures first in a benign medium and then exposing them to contaminants , 2007Costas et al 2001Costas et al , 2007Baos et al 2002;García-Villada et al 2002;FloresMoya et al 2005).…”
mentioning
confidence: 99%